Hambatan Struktural dan Administratif dalam Pemberian Bantuan Hukum Cuma-Cuma di Pengadilan Negeri Parepare - Ade Septian Ilyas; Muhammad Sabir; Wiwin Wiwin; Ardiyanti Aris; Moh Al Fatah Alti Putra (Jurnal Litigasi Amsir, 2025)
This study examines the implementation of free legal aid for economically disadvantaged communities at the Parepare District Court through a normative-empirical legal approach that combines analysis of statutory regulations with observation of their application in practice. The research highlights that legal aid institutions and court-based Legal Aid Posts (Posbakum) play a pivotal role in realizing the constitutional principle of equality before the law by ensuring that indigent defendants particularly those facing serious criminal charges receive professional legal assistance at no cost. The findings show that clear administrative requirements, such as identity documents, statements of indigence, and official poverty certificates, help target services to eligible recipients while supporting accountability and standardization across courts. At the same time, the study identifies significant obstacles, including limited financial and human resources, low legal literacy, complex bureaucracy, and unequal distribution of accredited advocates, which collectively hinder effective access to justice, especially in remote areas. These results underscore the need for stronger institutional support, increased budget allocation, enhanced supervision, and culturally sensitive legal education to optimize the role of legal aid as an instrument of social justice and the welfare state ideal in Indonesia.